1991
DOI: 10.1037/0022-3514.61.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Secondary identity enactments during hypnotic past-life regression: A sociocognitive perspective.

Abstract: In 4 studies. Ss received hypnotic suggestions to regress beyond birth to a previous life. In Study 1, the development of a past-life identity was unrelated to indexes of psychopathology. Studies 2 and 3 demonstrated that Ss developed past-life identities that reflected hypnotist-transmitted expectations. In Study 4 the credibility that Ss assigned to their past-life experiences was influenced by whether the hypnotist defined such experiences as reaiox imagined. Combined data from the first 3 studies indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 46 publications
(48 reference statements)
2
71
0
Order By: Relevance
“…Hypnosis, for example, may be used to treat some disorders such as smoking cessation (Wadden & Anderton, 1982). People's beliefs about the power of the thoughts revealed in hypnosis extend beyond the realm of the scientific, however, believing that the images that come to mind during hypnosis may offer evidence of past lives (Loftus, Garry, Brown, & Rader, 1994;Spanos, Menary, Gabora, DuBreuil, & Dewhirst, 1991). Similarly, while dreaming can serve to consolidate information in the service of problem solving (Stickgold & Walker, 2004;Wagner et al, 2004), lay beliefs about the insight revealed in dreams extends far beyond the intrapsychic information they might provide to the belief that the thoughts that occur in dreams can foretell the future (Morewedge & Norton, 2009).…”
Section: Which Spontaneous Thoughts Are Meaningful and When?mentioning
confidence: 99%
“…Hypnosis, for example, may be used to treat some disorders such as smoking cessation (Wadden & Anderton, 1982). People's beliefs about the power of the thoughts revealed in hypnosis extend beyond the realm of the scientific, however, believing that the images that come to mind during hypnosis may offer evidence of past lives (Loftus, Garry, Brown, & Rader, 1994;Spanos, Menary, Gabora, DuBreuil, & Dewhirst, 1991). Similarly, while dreaming can serve to consolidate information in the service of problem solving (Stickgold & Walker, 2004;Wagner et al, 2004), lay beliefs about the insight revealed in dreams extends far beyond the intrapsychic information they might provide to the belief that the thoughts that occur in dreams can foretell the future (Morewedge & Norton, 2009).…”
Section: Which Spontaneous Thoughts Are Meaningful and When?mentioning
confidence: 99%
“…Our ®ndings suggest that many individuals will report false memories when they are given a rationale from an authoritative source that makes the occurrence of such memories plausible, when they are provided with information that leads them to expect that they possess such memories, and when they are administered procedures that they believe will facilitate the recovery of their hidden memories. When these three conditions are met, people will report false memories of abductions by space aliens (Jacobs, 1992;Mack, 1994), past lives (Fiore, 1989;Wambach, 1979;Spanos et al, 1991), satanic ritual abuse (Young et al, 1991;Shaer and Cozolino, 1992), early childhood events Loftus and Pickrell, 1995), traumatic foetal experiences (Van Husen, 1988) and, as demonstrated in the present study, experiences occurring on the day after birth. That these three conditions frequently occur together during some types of abuse resolution therapy only serves to increase the risk of false memory reporting in patients who are exposed to them.…”
Section: Discussionmentioning
confidence: 75%
“…In response to this criticism, two studies (Loftus and Pickrell, 1995;Spanos et al, 1991) demonstrated the development of complex false memories in nonclinical contexts. With the aid of cooperating relatives who provided the relevant suggestions, Loftus and Pickrell (1995) in¯uenced participants to falsely remember that, at 5 years of age, they had been lost in a shopping mall.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In general, PLEs have received a mixture of interpretations and have been associated with a variety of phenomena that range from paranormal encounters (Braude, 2003;Chari, 1978;Grof, 1994, Hales, 2001a, 2001bLuke, 2011;Stevenson, 1977) and altered states of consciousness (Luke, 2011;Simöes, 2002;Tart, 1974Tart, , 1992Woolger, 1999) to fantasy constructions (Baker, 1982;Dwairy, 2006;Kampman, 1976;Mariott, 1984;Robertson & Gow, 1999;Spanos, 1988Spanos, , 1996Spanos, Menary, Gabora, DuBreuil, & Dewhirst, 1991;Venn, 1986;Wickramasekera, 2009), repressed memories (Loftus, 1997(Loftus, , 2000Pasricha, 2011) or genetic memories (Almeder, 1992;Pasricha, 2006;Stevenson, 1987;Tarazi, 1990), and some others.…”
Section: International Journal Of Transpersonal Studies 84mentioning
confidence: 99%